La terapia de reminiscencia para mejorar el autoestima de los adultos mayores con discapacidad física, que asisten al centro de día San José, de la ciudad de Loja. Periodo 2013-2014 - Sarango Cuenca, Jinmy Alberto (2015)
The research was headed with the purpose of applying the reminiscence therapy to improve the self-esteem of Older Adults with Physical Disabilities that attend to the “San Jose Center” of the Loja city. To carry on the research were used the following methods: analytical, synthetic, inductive, descriptive, and quantitative – qualitative; instruments such as the Rosenberg Self-Esteem Scale Test and Application of Reminiscence Therapy. As a result of the research was determined: That the sample of 8 Ages Adults with Physical Disabilities were found with Low Self-Esteem and during application of the techniques of Case Souvenir Book or book Autobiographical Memory and Historical Data Partner or Cultural, it had a progressive improvement in the level of very good and reevaluation most encounters a High Self-Esteem. Front to the advice on these findings center officials to take this model of therapy in daily activities to improve the quality of life. Reminiscence Therapy can build self-confidence and lift the spirits of the elderly. It is reactivated memory, stir the memory, the use of practices that stimulate their ability to introspective and thought.